2017
DOI: 10.1159/000454697
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Ablation in the Management of Colorectal Cancer Patients with Oligometastatic Liver Disease

Abstract: Background: Surgical resection of limited colorectal liver disease improves long-term survival and can be curative in a subset of selected cases. Image-guided percutaneous ablation therapies have emerged as safe and effective alternative options for selected patients with unresectable colorectal liver metastases (CLM) that can be ablated with margins. Ablation causes focal destruction of tissue and has increasingly been shown to provide durable eradication of tumors. Methods: A selective review of literature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Data on oligometastases of lung cancer have frequently been reported [21,22,23]. Oligometastatic prostate cancer and oligometastatic liver disease in colorectal cancer are also often discussed [5,24,25,26]. So far, malignant melanoma and malignancies of the cervix and breast are reported less frequently in the context of oligometastasis [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Data on oligometastases of lung cancer have frequently been reported [21,22,23]. Oligometastatic prostate cancer and oligometastatic liver disease in colorectal cancer are also often discussed [5,24,25,26]. So far, malignant melanoma and malignancies of the cervix and breast are reported less frequently in the context of oligometastasis [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous ablation techniques can be performed with curative intent for primary and secondary liver tumors. Several ablation methods are known to have tumoricidal effects: chemical injection of alcohol, heating, cooling, and irreversible electroporation or electrochemotherapy (5)(6)(7)(8). Under imaging guidance such as ultrasound, CT, MRI, or PET/CT, percutaneous ablation can be performed effectively ( Fig.…”
Section: Rationale and Treatment Selectionmentioning
confidence: 99%
“…1 Thermal ablations has played an increasing role over the last few decades in the palliative and curative setting of colorectal liver metastases (CRLMs) in nonsurgical candidates with liver-predominant disease. 2 Almost 20 years ago, in a landmark paper, Solbiati et al 3 reported survival outcomes after CRLMs comparable with surgery (93, 69, and 46% at 1, 2, and 3 years, respectively). Results improved when small lesions (<4 cm in diameter) could be treated with broad tumor-free margins (5 mm).…”
mentioning
confidence: 99%
“…4 These findings were confirmed by several papers that developed a solid awareness about the advantages and the efficacy of thermal ablation (►Table 1). 2,[5][6][7][8][9][10] Further combined approaches such as ablations performed between staged hepatectomies or after neoadjuvant chemotherapy [11][12][13][14][15] have expanded and consolidated their role in the management of CRLMs.…”
mentioning
confidence: 99%